Reception of Malthusian theory in Georgian and Russian literature of the XIX century - Chogovadze, Lela (The International tax journal, 2024)
The Malthusian theory, originating from Thomas Robert Malthus's seminal work "An Essay on the Principle of Population" (1798), posits thatpopulation growth tends to outpace the growth of resources necessary to sustain it, leading to inevitable checks such as famine, disease, and conflict. This theory has significantly influenced world literature, serving as a thematic backbone in various narratives that explore the tension between human aspiration and environmental or societal limitations. In literature, Malthusian concepts are often employed to critique socio-economic structures, explore dystopian futures, and reflect on historical events characterized by scarcity and struggle. This paper examines the manifestation of Malthusian theory across different literary traditions and genres, highlighting its impact on character development, plot progression, and thematic depth. By analyzing key texts from diverse cultural backgrounds, the study aims to illustrate how Malthusian ideas continue to resonate in contemporary literature, offering critical insights into the ongoing dialogue between human ambition and the finite nature of resources.